Critique of values by Martin Heidegger and Friedrich Nietzsche - Augustyniak, Piotr (Journal of Public Governance, 2018)
The paper is an attempt to show the basic features of the critique of thinking based on values, which is an essential part of Martin Heidegger’s thought. In order to present his opinions clearly, they are confronted with the critique of values that Friedrich Nietzsche presents in his work “Thus Spoke Zarathustra”. The author argues that thinking based on values is in service of the modern subjectivity, which is expansive and egological. However, unlike Heidegger, the author tries to explore a concept of value which would be free of such an egological tendency. His inspiration is Nietzsche, who wrote about ‘new values’, and related them with creativity which leads the subject to transgression.